Design and evaluation of a novel triaxial isometric trunk muscle strength measurement system - Azghani, M R; Farahmand, F; Meghdari, A; Vossoughi, G; Parnianpour, M (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2009)
Abstract Maximal strength measurements of the trunk have been used to evaluate the maximum functional capacity of muscles and the potential mechanical overload or overuse of the lumbar spine tissues in order to estimate the risk of developing musculoskeletal injuries. A new triaxial isometric trunk strength measurement system was designed and developed in the present study, and its reliability and performance was investigated. The system consisted of three main revolute joints, equipped with torque sensors, which intersect at L5—S1 and adjustment facilities to fit the body anthropometry and to accommodate both symmetric and asymmetric postures in both seated and standing positions. The dynamics of the system was formulated to resolve validly the moment generated by trunk muscles in the three anatomic planes. The optimal gain and offset of the system were obtained using deadweights based on the least-squares linear regression analysis. The R2 results of calibration for all loading courses of all joints were higher than 0.99, which indicated an excellent linear correlation. The results of the validation analysis of the regression model suggested that the mean absolute error and the r.m.s. error were less than 2 per cent of the applied load. The maximum value of the minimum detectable change was found to be 1.63 N m for the sagittal plane torque measurement, 0.8 per cent of the full-scale load. The trial-to-trial variability analysis of the device using deadweights provided intra-class correlation coefficients of higher than 0.99, suggesting excellent reliability. The cross-talk analysis of the device indicated maximum cross-talks of 1.7 per cent and 3.4 per cent when the system was subjected to flexion—extension and lateral bending torques respectively. The trial-to-trial variability of the system during in-vivo strength measurement tests resulted in good to excellent reliability, with intra-class correlation coefficients ranging from 0.69 to 0.91. The results of the maximum voluntary isometric torques exertion measurements for 30 subjects indicated good agreement with the previously published data in the literature. The extensive capabilities and high reliability of the system are promising for more comprehensive investigations on the trunk biomechanics in future, e.g. isometric strength measurement at symmetric and asymmetric postures, muscle endurance, and recruitment pattern analysis.